Artikel Kehormatan: Symphonizing Intellectual Property Laws in the Advancement of Culture - Agus Sardjono (Faculty of Law, Universitas Padjadjaran, 2017)
The Indonesian Government has enacted the Law on Advancement of Culture. This Law is themanifestation of the trust bestowed by the Indonesian Constitution, entrusting the state to advance theIndonesian culture. This Law is the guideline and ideals for the Indonesian Government and the societyat large in conducting efforts to advance culture. The purpose is so that there is a clear direction in theefforts to develop, utilize, promote, and preserve and protect Indonesian culture in the face ofglobalization and digitalization of world culture. At the very least, this law facilitates individuals who arepart of the society, to be more creative in their art and to be rewarded through rights protection. Theexistence of these two types of laws must create a favorable environment in the efforts of advancingculture. Like an orchestra displaying a beautiful symphony, intellectual property laws and the law ofcultural advancement are also a beautiful symphony in the framework of advancing Indonesian culturein hopes for it to provide an important contribution in human civilization. This paper tries to expresshow the efforts to symphonize the two laws must be done in an assessment that is prescriptivedoctrinal.Simfonisasi Hukum Kekayaan Intelektual dalam Pemajuan KebudayaanAbstrakPemerintah Indonesia telah menetapkan Undang-Undang Pemajuan Kebudayaan sebagai bentuk penjelmaan kepercayaan yang diberikan oleh Konstitusi Indonesia kepada negara untuk menjadi pelaksanaan pemajuan kebudayaan Indonesia. UU tersebut merupakan pedoman serta cita-cita Pemerintah Indonesia dan masyarakat dalam upaya pelaksanaan pemajuan kebudayaan, dengan tujuan sebagai petunjuk dalam mengembangkan, menggunakan, mempromosikan, menjaga, dan melestarikan kebudayaan Indonesia di hadapan globalisasi dan digitalisasi dunia kebudayaan. UU ini juga sekiranya telah memfasilitasi anggota masyarakat untuk menjadi lebih kreatif dalam sisi seni dan turut diberikan perlindungan hak kepadanya. Keberadaan UU ini harus mampu menyediakan lingkungan yang memadai guna mendorong pemajuan kebudayaan. Layaknya suatu orkestra menghasilkan simfoni yang indah, hukum kekayaan intelektual dan hukum pemajuan kebudayaan juga merupakan simfoni peraturan dalam mewujudkan pemajuan kebudayaan Indonesia guna memberikan kontribusi penting dalam kehidupan manusia. Artikel ini akan membahas bagaimana cara simfonisasi hukum kekayaan intelektual dilaksanakan dalam perspektif doktrin hukum.DOI: https://doi.org/10.22304/pjih.v4n3.a1